2018
DOI: 10.3855/jidc.9643
|View full text |Cite
|
Sign up to set email alerts
|

Dientamoeba fragilis diagnosis by fecal screening: relative effectiveness of traditional techniques and molecular methods

Abstract: Introduction: Dientamoeba fragilis, an intestinal trichomonad, occurs in humans with and without gastrointestinal symptoms. Its presence was investigated in individuals referred to Milad Hospital, Tehran. Methodology: In a cross-sectional study, three time-separated fecal samples were collected from 200 participants from March through June 2011. Specimens were examined using traditional techniques for detecting D. fragilis and other gastrointestinal parasites: direct smear, culture, formalin-ether concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…In the present study, when we compared age, gender and common GI symptoms between the four groups, no statistically significant difference was noted. A number of studies reported no relation between gender and Blastocystis infection, as well as D. fragilis infection, supporting our findings (33,34). A case control study reported that GI symptoms were more common in cases without D. fragilis or Blastocystis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, when we compared age, gender and common GI symptoms between the four groups, no statistically significant difference was noted. A number of studies reported no relation between gender and Blastocystis infection, as well as D. fragilis infection, supporting our findings (33,34). A case control study reported that GI symptoms were more common in cases without D. fragilis or Blastocystis.…”
Section: Discussionsupporting
confidence: 90%
“…A study reported frequency of D. fragilis with direct smear, formalin-ether concentration, culture, permanent staining and amplification of SSU rRNA and 5.8S rRNA genes. The positive rates with the methods were as follows: 0%, 0%, 1%, 5%, 6% and 13.5%, respectively (33).…”
Section: Discussionmentioning
confidence: 92%
“…Permanently staining methods or cultivation procedures are often required to achieve a correct parasitological diagnosis. This fact confirms that the nucleic acidbased assays have been the diagnostic method of choice for D. fragilis in feces [10].…”
Section: Introductionsupporting
confidence: 72%
“…[ 14 ] On the contrary, Dientamoeba was not found by direct smear or formalin-ether concentration methods as stated by Hamidi et al . [ 24 ] Previous studies reported that identification and differentiation of Dientamoeba by direct smear and formalin-ether concentration techniques lack accuracy and are laborious and time-consuming compared to molecular assays. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%